A new integrative approach to assess aortic stenosis burden and predict objective functional improvement after TAVR - de la Torre Hernandez, Jose M.; Veiga Fernandez, Gabriela; Ben-Assa, Eyal; Sainz Laso, Fermin; Lee, Dae-Hyun; Ruisanchez Villar, Cristina; Lerena, Piedad; Garcia Camarero, Tamara; Cuesta Cosgaya, Jose M.; Fradejas-Sastre, Victor; Benito, Mercedes; Barrera, Sergio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background A non-negligible rate of patients undergoing transcatheter aortic valve replacement (TAVR) do not report symptomatic improvement or even die in the short-midterm. We sought to assess the degree of objective functional recovery after TAVR and its prognostic implications and to develop a predictive model. Methods In a cohort of patients undergoing TAVR, a prospective evaluation of clinical, anatomical, and physiological parameters was conducted before and after the procedure. These parameters were derived from echocardiography, non-invasive analysis of arterial pulse waves, and cardiac tomography. Objective functional improvement 6 months after TAVR was assessed using a 6-min walk test and nitro-terminal pro-brain natriuretic peptide (NT-proBNP) levels. The derived predictive model was prospectively validated in a different cohort. A clinical follow-up was conducted at 2 years. Results Among the 212 patients included, objective functional improvement was observed in 169 patients (80%) and subjective improvement in 187 (88%). Patients with objective functional improvement showed a much lower death rate at 2 years (9% vs. 31% p = 0.0002). Independent predictors of improvement were as follows: mean aortic gradient of ≥40 mmHg, augmentation index75 of ≥45%, the posterior wall thickness of ≤12 mm, and absence of atrial fibrillation. A simple integer-based point score was developed (GAPA score), which showed an area under the curve of 0.81 for the overall cohort and 0.78 for the low-gradient subgroup. In a validation cohort of 216 patients, these values were 0.75 and 0.76, respectively. Conclusion A total of 80% of patients experienced objective functional improvement after TAVR, showing a significantly lower 2-year mortality rate. A predictive score was built that showed a good discriminative performance in overall and low-gradient populations.